2011
DOI: 10.1177/1741826711422505
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle risk reduction interventions in atrial fibrillation: a systematic review

Abstract: Literature suggests risk reduction interventions for AF can improve exercise levels, HRQoL and reduce HR, but the evidence base is small, methodologically compromised and focused on physical functioning. High-quality research in this area is required in order to help the multitudes of people living with AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 53 publications
0
16
0
1
Order By: Relevance
“…20,23,24 Here, our data showed that the qualitative investigations as waist, hip circumference decrease but not the weight, BMI or FAT mass. This data is important due this two points are more associated with cardiovascular diseases than the fat mass or BMI.…”
Section: Resultsmentioning
confidence: 69%
“…20,23,24 Here, our data showed that the qualitative investigations as waist, hip circumference decrease but not the weight, BMI or FAT mass. This data is important due this two points are more associated with cardiovascular diseases than the fat mass or BMI.…”
Section: Resultsmentioning
confidence: 69%
“…Patients with fewer documented risk factors in the current study were less likely to be referred to Phase II CR, and therefore they were missing out on receiving appropriate, effective treatments . Given the growing body of evidence for the benefits of structured exercise, such as that included in Phase II CR, for AF patients' exercise capacity and HRQoL, this is an important deficit . Further research is required that tests the effectiveness of multidisciplinary CR in AF patients.…”
Section: Discussionmentioning
confidence: 94%
“…Aside from the minor proportion of AF diagnoses due to excessive exercise and caffeine intake, the majority of modifiable risk factors are common to all cardiovascular diseases. These factors include hypertension, hypercholesterolaemia, diabetes, smoking, obesity and sedentary behaviour . Screening and interventions to support modification of these risk factors are warranted for this population.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, Lowres et al 1 demonstrated that lifestyle interventions offer considerable promise for addressing the growing health needs of AF patients. Despite this, the authors also identified a current shortage of effective intervention programs.…”
Section: Future Care Provision: Toward Amalgamated Accessible Cardiacmentioning
confidence: 97%